The Position of the Consequential Loss in the Iranian and English Legal Systems - Mojtaba Zamani; Soheil Taheri; Pezhman Pirouzi; Alireza Alireza Mazloom Rahni (آموزه‌‌های فقه مدني, 2022)
The realization of the civil liability requires three pillars: the pillar of loss, damaging action and the causal nexus between the damage and the incident (causation). The “loss” element is more important than the others. Generally, law views “loss” compensable when it has certain conditions and criteria as in the Iranian legal system “the direct loss” and in English legal system “loss being too remote” is of the conditions of the recoverable losses which have been introduced. In the Iranian legal system if a harm and loss in indirect way and through intermediary is caused injury to a body or property it is not recoverable and its reason is there is doubt in attributing the indirect loss to the agent of loss. The approach of The Iranian legal system and English legal system to the indirect damages is not the same. The concept of indirect loss in the Iranian legal system relates to the pillar of causation while in English law has a close relation to the reasonably foreseeable principle. In the Iranian legal system, it is a principle that indirect loss is not recoverable but in English law in most cases is recoverable. Meanwhile determining the position of indirect loss the present paper has propounded the possibility of the compensation of indirect loss under some certain circumstances in the legal Iranian system.